PEG hydrogel sealant versus fibrin glue in posterior fossa surgery: an economic comparison across five European countries - Giuseppe Talamonti; Jorn-Andre Horaczek; Rafael Torrejon Torres; Lisa Da Deppo; Marissa J Carter (Becaris Publishing Limited, 2024)
Aim: Posterior cranial fossa (PCF) surgery is associated with complications, including cerebrospinal fluid (CSF) leakage. Dural sealants such as polyethylene glycol (PEG)-based hydrogels and fibrin glue can prevent CSF leaks, with evidence suggesting PEG hydrogels may outperform fibrin glue. However, the budget impact of using PEG hydrogels in PCF surgeries in Europe is unclear. Materials & methods: A decision tree was developed based on a previous US model, to assess the budget impact of switching from fibrin glue to PEG hydrogel in PCF surgery across five European countries. Input costs were derived from published sources for the financial year 2022/2023. Health outcomes, including CSF leaks, were considered. Results: The model predicted that using PEG hydrogel instead of fibrin glue in PCF surgery can lead to cost savings in five European countries. Cost savings per patient ranged from EUR 419 to EUR 1279, depending on the country. Sensitivity analysis showed that the incidence of CSF leaks and pseudomeningoceles had a substantial impact on the model's results. Conclusion: PEG hydrogels may be a cost-effective alternative to fibrin glue in PCF surgery. The model predicted that cost savings would be mainly driven by a reduction in the incidence of postoperative CSF leaks, resulting in reduced reliance on lumbar drains, reparative surgery and shortened hospital stays.